The Niger Delta and oil politics - Ekpo, Udeme (Lagos : International Energy Communications, 2004)
This book is the most authoritative, factual, sequential, balanced and up-to-date work ever done on the petroleum industry, the Niger Delta and Nigeria.
Includes bibliographical references (p. 256-261) and index.
aug 09/05/13
Loans
Keywords: Petroleum industry and trade; Niger River Delta (Nigeria)